The Role of Suburban Government in the City-Building Process: The Case of Notre Dame de Grâces, Quebec, 1876-1910 - Van Nus, Walter (Urban History Review / Revue d'histoire urbaine, 1984)
Annexation of adjacent municipalities was a growth strategy crucial to both Montreal and Toronto. The importance of the pre-annexation history of a suburb such as Maisonneuve, a major industrial city when Montreal absorbed it in 1918, is obvious. Little, however, has been written on suburbs lacking an industrial base. This paper demonstrates that the government of a sparsely populated, almost entirely residential suburb could take decisions which continued to shape development long after annexation.Annexed in 1910, the Town of Notre Dame de Grâces had been intended by its founders to become a residential haven for the middle class. The population of Notre Dame de Grâces Ward grew quickly, from 4,000 in 1910 to 46,850 in 1931. By the 1920s, it was recognized as the preferred residential location for middle-income, white-collar anglophones. It welcomed only the financially reliable: those who lost their jobs typically moved to cheaper quarters elsewhere, leaving the area with fewer indigents than any other ward in Montreal. Popularly known as "N.D.G.," its success came in part from favourable location. It was situated mainly on the far reaches of the western slope of Mount Royal, "above the hill," elevated above the smoky industrial area along the Lachine Canal by the bluff which runs for miles. Moreover, the independent City of Westmount, equally residential but wealthier, sheltered N.D.G. from downtown bustle. Nonetheless, N.D.G.'s pre-annexation government determined when suburban growth might "take off," the land use, the economic level of new inhabitants, and about what axis builders would concentrate the best homes.